2018
DOI: 10.35608/ruraled.v30i1.456
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions of their Preparation for Teaching Linguistically and Culturally Diverse Learners in Rural Eastern North Carolina

Abstract: The number of English language learners (ELL) students in the US is increasing dramatically. The growth is even more evident in rural areas of the United States such as North Carolina where teachers are facing classrooms with a majority of second language learners. The authors conducted a study interviewing 24 teachers at a rural elementary school in eastern North Carolina. Teachers were interviewed regarding their perceptions of their preparedness to teach English language learners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Further, it is estimated that more than 35% of these students in public schools will be coming from households in which a language other than English is spoken in the home. This is particularly relevant to the rural context in which the growth is more evident as large numbers of Latinos who were previously migrant farm workers seek opportunities to establish permanent homes, often in rural areas (O'Neal, Ringler, & Rodriguez, 2008;Smith, Stern, & Shatrova, 2008). Overall, there has been a change from immigrants settling in mostly urban areas to immigrants choosing a wider range of contexts in which to live (Stufft & Brogadir, 2010).…”
Section: Trends In Population Shiftsmentioning
confidence: 94%
See 2 more Smart Citations
“…Further, it is estimated that more than 35% of these students in public schools will be coming from households in which a language other than English is spoken in the home. This is particularly relevant to the rural context in which the growth is more evident as large numbers of Latinos who were previously migrant farm workers seek opportunities to establish permanent homes, often in rural areas (O'Neal, Ringler, & Rodriguez, 2008;Smith, Stern, & Shatrova, 2008). Overall, there has been a change from immigrants settling in mostly urban areas to immigrants choosing a wider range of contexts in which to live (Stufft & Brogadir, 2010).…”
Section: Trends In Population Shiftsmentioning
confidence: 94%
“…Rural teachers often have a range of roles within the school and community (Wenger, Dinsmore, & Villagómez, 2012), including providing valuable support services for families. However, rural teachers do not necessarily feel prepared to serve the needs of English Language Learners (O'Neal et al, 2008;Stufft & Brogadir, 2010). In rural contexts, if the teachers do not represent the languages and cultures of their Downloaded by [Fondren Library, Rice University] at 14:14 10 June 2016 families, there may be some obstacles to all students and families having a comfort level to access, let alone have an awareness of, available services and opportunities.…”
Section: The Value Of Diversifying the Education Workforcementioning
confidence: 96%
See 1 more Smart Citation
“…Studies involving rural schools have found that most rural teachers received little to no training on how to adapt instruction for ELs and perceived themselves as being unprepared to teach these students (O’Neal et al, 2008). Although the struggle to effectively teach ELs is not exclusive to rural teachers, the challenges faced by these educators tend to be exacerbated by the historical underfunding of rural schools (Yettick et al, 2014), as well as the difficulties that rural school districts usually have to recruit and retain special education or EL education professionals and to offer adequate PD to staff teaching ELs due to isolation and limited resources (Lavalley, 2018).…”
Section: Responding To the Needs Of English Learnersmentioning
confidence: 99%
“…Currently, ELs outnumber students with disabilities in the public schools. Perhaps not unexpectedly, investigations across the United States show that both current and future teachers feel unprepared to educate ELs (O'Neal, Ringler, & Rodriguez, ; Siwatu, ). To compound this predicament, only three states (6%)—Arizona, Florida, and New York—require pre‐service educators to obtain training in EL instruction to be certified to teach (Arizona and Florida are represented in the present study; U.S. Department of Education, National Center for Education Statistics, State Education Reforms, 2009).…”
mentioning
confidence: 99%